1999
DOI: 10.1080/10473289.1999.10463915
|View full text |Cite
|
Sign up to set email alerts
|

Particulate Air Pollution in Mexico City: A Collaborative Research Project

Abstract: PM, PM, precursor gas, and upper-air meteorological measurements were taken in Mexico City, Mexico, from February 23 to March 22, 1997, to understand concentrations and chemical compositions of the city's particulate matter (PM). Average 24-hr PM concentrations over the period of study at the core sites in the city were 75 H g/m. The 24-hr standard of 150 μ g/m was exceeded for seven samples taken during the study period; the maximum 24-hr concentration measured was 542 μ g/m. Nearly half of the PM was compose… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
92
1

Year Published

2000
2000
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 133 publications
(97 citation statements)
references
References 7 publications
4
92
1
Order By: Relevance
“…Consistent (r = 0.95) and linear relationships (SO 4 2-vs. S slope = 2.98 ± 0.08, intercept = -0.07 ± 0.17 µg/m 3 ) were found between water-soluble SO 4 2-and total S measurements, indicating that most S was of secondary origin and was probably neutralized by NH 3 . SO 4 2-was estimated from S measurements at the 12 sites with the single-filter-pack sampling configuration. The stoichiometric ratios of NH 4 , SO 4 2-, and NO 3 -were used to calculate (NH 4 ) 2 SO 4 and NH 4 NO 3 concentrations.…”
Section: Spatial Patterns Of Pm 10 Componentsmentioning
confidence: 80%
See 2 more Smart Citations
“…Consistent (r = 0.95) and linear relationships (SO 4 2-vs. S slope = 2.98 ± 0.08, intercept = -0.07 ± 0.17 µg/m 3 ) were found between water-soluble SO 4 2-and total S measurements, indicating that most S was of secondary origin and was probably neutralized by NH 3 . SO 4 2-was estimated from S measurements at the 12 sites with the single-filter-pack sampling configuration. The stoichiometric ratios of NH 4 , SO 4 2-, and NO 3 -were used to calculate (NH 4 ) 2 SO 4 and NH 4 NO 3 concentrations.…”
Section: Spatial Patterns Of Pm 10 Componentsmentioning
confidence: 80%
“…Figure 4 shows that S concentrations in the city center and northern portion were ~10% higher than in other areas, with higher concentration gradients found around the Xalostoc site. Secondary SO 4 2-that forms in the atmosphere was more homogeneously distributed throughout the area than were the primary emissions from dust and vehicle exhaust. Spatial correlations of NH 3 were high (r > 0.8) for sites surrounding the La Merced site (G12, G17, G20, G21, G22, G23, G25, G26, and G27).…”
Section: Correlationsmentioning
confidence: 98%
See 1 more Smart Citation
“…Schwartz 8 examined daily deaths and hospital admissions in Chicago for 1988-1993 and found that PM less than 10 µm in aerodynamic diameter (PM 10 ) was associated with increased daily deaths and hospital admissions. Fine particulate measurement and source apportionment have been studied throughout the world, including in Australia, 9 Chile, 10 Mexico, 11 and central Europe. 12 The proportion of smaller particles is especially important in the estimation of health risk.…”
Section: Introductionmentioning
confidence: 99%
“…The first of these was the Mexico City Air Quality Research ]. The IMADA program obtained improved data on the spatial patterns of aerosols in Mexico City [Edgerton et al 1999] and improved spatial information on the evolution of vertical wind and temperature structure in the Mexico Basin. Fast and Zhong [1998] used data from this experiment to link boundary layer circulation patterns to the observed spatial ozone distribution patterns in the basin by studying seven pollution episodes during the IMADA-AVER experiment using a high-resolution mesoscale meteorological model and a Lagrangian particle dispersion model.…”
Section: Introductionmentioning
confidence: 99%